2018
DOI: 10.3329/kyamcj.v9i2.38145
|View full text |Cite
|
Sign up to set email alerts
|

Parathyroid hormone assay in total thyroidectomy

Abstract: Background: Total thyroidectomy is commonly practice now-a-days for either malignant or benign multinodular goitre. And post-operative hypocalcaemia is a squeal in this operation.Objectives: To find out whether post-operative PTH level is a parameter to identify hypocalcaemia after total thyroidectomy.Materials & Methods: This study was carried out from July 2013 to July 2014 in department of Surgery Sir Salimullah Medical College & Mitford Hospital. Total 116 patients were selected. PTH assay was perf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…The effect of calcitonin is expected early, as its half-life is two to 15 minutes (P. Yu et al, 2019). Li et al, (2021), Hamed & Afifi, (2019) and Sharif et al, (2018) showed that there was no significant change in postoperative calcitonin when comparing patients with hypo-or normocalcemia (Hamed & Afifi, 2019;Li, Rogers, & Rehman, 2021;Sharif, Ali, Rahman, Siddique, & Rahman, 2018).…”
Section: Calcitoninmentioning
confidence: 94%
“…The effect of calcitonin is expected early, as its half-life is two to 15 minutes (P. Yu et al, 2019). Li et al, (2021), Hamed & Afifi, (2019) and Sharif et al, (2018) showed that there was no significant change in postoperative calcitonin when comparing patients with hypo-or normocalcemia (Hamed & Afifi, 2019;Li, Rogers, & Rehman, 2021;Sharif, Ali, Rahman, Siddique, & Rahman, 2018).…”
Section: Calcitoninmentioning
confidence: 94%